2023
DOI: 10.1021/acsami.3c05272
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Encapsulation on the Efficiency and Positive Aging Behavior in Blue Quantum Dot Light-Emitting Devices

Abstract: Encapsulating blue quantum dot light-emitting devices (QLEDs) using an ultraviolet curable resin is known to lead to a significant increase in their efficiency. Some of this efficiency increase occurs immediately, whereas some of it proceeds over a period of time, typically over several tens of hours following the encapsulation, a behavior commonly referred to as positive aging. The root causes of this positive aging, especially in blue QLEDs, remain not well understood. Here, it is revealed that contrary to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For instance, the fresh device had a current density of 121 mA/cm^2 at 6V, while the aged devices showed 280, 480, and 520 mA/cm^2 at 6V for day 1, day 3, and day 4, respectively. Previous reports from Qiang et al, Acharya et al, and Chen et al have shown that the aging process significantly improves the current density of QLEDs by forming a thin AlOx interlayer among the ZnMgO/Al interface through the aging process [20][21][22] . Which suppresses the electron injection barrier and increases the conductivity of ZnMgO by creating oxidation deficiency in ZnMgO.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the fresh device had a current density of 121 mA/cm^2 at 6V, while the aged devices showed 280, 480, and 520 mA/cm^2 at 6V for day 1, day 3, and day 4, respectively. Previous reports from Qiang et al, Acharya et al, and Chen et al have shown that the aging process significantly improves the current density of QLEDs by forming a thin AlOx interlayer among the ZnMgO/Al interface through the aging process [20][21][22] . Which suppresses the electron injection barrier and increases the conductivity of ZnMgO by creating oxidation deficiency in ZnMgO.…”
Section: Resultsmentioning
confidence: 99%
“…17–19 Specifically, significant advances in the stability of QLEDs have been reported through a remarkable phenomenon called “positive aging,” which accompanies post-treatments such as thermal annealing or acidic resin treatment. 20–28 In general, QLEDs exhibit negative aging behavior owing to the rapid deterioration of the charge transporting layers, where the luminance continuously decreases as a function of time. 29–32 In contrast, QLEDs exhibiting positive aging overcome the rapid luminance decline in the initial stage of device operation and offer drastically extended lifetimes; 20,25 however, the precise principle of positive aging remains unclear.…”
Section: Introductionmentioning
confidence: 99%